A study on understanding the child behaviour and their Psychology in nuclear families - Rashmi Kulkarni; K. Sujatha; C. Laya Sree; A. Sneha (PT Agung Media Publisher, 2024)
Families with a mother and father who reside together with biologically related children remain a common setting for socializing school-age youngsters in our society. A much debated, but common presumption in the existing scholarship is that these nuclear families are the optimal environments for children against which the efficacy of all other types of families are measured. The objectives of my study are to understand the psychology of children behaviour, and to understand the best learning resources for behavioral changes. The need of the study is to Unique Family Dynamics, Parenting Challenges and Strategies, Impact on Child Well-being, Socialization and Peer Relationships, Socialization and Peer Relationships, Socialization and Peer Relationships. The purpose of our study is to identify risk factors and protective factors, promote mental health and well-being, improve family relations, inform policy and practice. This study delves into the intricate realm of child behaviour within the context of nuclear family structures. With the prevalent societal shift towards smaller family units, understanding the dynamics influencing children's behavioural patterns becomes imperative. This qualitative inquiry aims to elucidate the multifaceted factors that shape child behaviour in nuclear families, thereby contributing to a nuanced comprehension of familial dynamics in contemporary society. This study not only contributes to theoretical understandings of family dynamics but also offers practical implications for parents, educators, and mental health professionals. This research aims to foster supportive environments that promote positive developmental outcomes for children growing up in such familial contexts.